Everyday Real-Time Marketing: A (G)local Communication Antidote for Increasing Self-Brand Connection and Brand Usage Intent - Santos, Carolina Gomes Martinho Marques dos (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence